2014
DOI: 10.3109/10409238.2014.889651
|View full text |Cite
|
Sign up to set email alerts
|

A review of xylan and lignin biosynthesis: Foundation for studying Arabidopsisirregular xylemmutants with pleiotropic phenotypes

Abstract: Plant cells are surrounded by a carbohydrate-rich extracellular matrix known as the cell wall. Primary cell walls are laid down around dividing and elongating cells and consist largely of the polysaccharides cellulose, hemicelluloses, and pectin along with approximately 10% protein. Specific cells such as xylem vessels and fibers lay down a secondary wall rich in cellulose, hemicellulose, and lignin, with lesser amounts of pectin. Most of the models depict the plant cell wall as a matrix of separate polysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 304 publications
2
76
0
1
Order By: Relevance
“…2). This may be due to IRX10 functional variations between plant species and/or differences in the heterologous expression systems (for review, see Hao and Mohnen, 2014). Similarly, expression of AoIRX14A also was capable of adding a single Xyl residue to the Xyl 5 -AA acceptor.…”
Section: The Xsc Is Located In the Lumen Of The Gamentioning
confidence: 99%
See 2 more Smart Citations
“…2). This may be due to IRX10 functional variations between plant species and/or differences in the heterologous expression systems (for review, see Hao and Mohnen, 2014). Similarly, expression of AoIRX14A also was capable of adding a single Xyl residue to the Xyl 5 -AA acceptor.…”
Section: The Xsc Is Located In the Lumen Of The Gamentioning
confidence: 99%
“…Additionally, the reducing end (RE) sequence of heteroxylans from dicots and gymnosperms differs from that of grasses. In the dicots/gymnosperms, it is a characteristic tetrasaccharide glycosyl sequence, b-D-Xylp-(1→3)-a-L-Rhap-(1→2)-a-D-GalpA-(1→4)-D-Xylp, that is absent in the grasses (for review, see Hao and Mohnen, 2014). Recently, Ratnayake et al (2014) reported that the RE glycosyl sequence of wheat (Triticum aestivum) endosperm arabinoxylan constitutes a linear (1→4)-b-DXylp backbone that may be monosubstituted either with an a-L-Araf residue at the RE b-D-Xylp residue and/or the penultimate RE b-D-Xyl residue or with an a-D-GlcpA residue at the RE b-D-Xylp residue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the paralogs IRX14 and IRX14L also encode members of the GT43 family. IRX9 and IRX14 play major, nonredundant roles in xylan backbone elongation required for GX biosynthesis (Hao and Mohnen, 2014), although their presumed functions as xylan:xylosyltransferases with GT enzymatic activity has recently been called into question (Ren et al, 2014). Genetic evidence suggests that IRX9 and its paralog IRX9L, as well as IRX14 and its paralog IRX14L, encode pairs of proteins with the same functions in the biosynthesis of the xylan backbone (Lee et al, 2011;Keppler and Showalter, 2010;Wu et al, 2010).…”
Section: Role Of Xylan Polysaccharide Primexinementioning
confidence: 99%
“…Arabidopsis mutants defective in xylan biosynthesis typically exhibit irx phenotypes characterized by collapsed vessel elements (Hao and Mohnen, 2014), which suggests a key role for GX in secondary cell wall structure and function. The SPG2 locus, identified by its spg exine patterning phenotype (Dobritsa et al, 2011) is synonymous to IRX9L, which, like IRX9, encodes a member of the GT43 family of GTs (Peña et al, 2007;Wu et al, 2010).…”
Section: Role Of Xylan Polysaccharide Primexinementioning
confidence: 99%